2022
DOI: 10.3390/cancers14030718
|View full text |Cite
|
Sign up to set email alerts
|

Management of Oligoprogression in Patients with Metastatic NSCLC Harboring ALK Rearrangements

Abstract: Personalized treatment based on driver molecular alterations, such as ALK rearrangement, has revolutionized the therapeutic management of advanced oncogene-addicted NSCLC patients. Multiple effective ALK tyrosine kinase inhibitors (TKIs), with the amelioration of the activity at central nervous system level, are now available, leading to substantial prognosis improvement. The exposure to TKIs triggers resistance mechanisms and the sequential administration of other TKIs and chemotherapy is, for the most part, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Oncogenic receptor tyrosine kinases are definitive drug therapy targets for the treatment of NSCLC patients containing gene mutations, especially EGFR mutations and ALK rearrangements that are targets of the precision medicine management of chest neoplasms [ 149 , 150 ]. A meta-data analysis showed that individuals who never smoked were more susceptible to the EGFR and ALK-EML4 mutations than ever-smokers [ 3 ].…”
Section: The Impact Of Cur Analogs On Nsclcmentioning
confidence: 99%
“…Oncogenic receptor tyrosine kinases are definitive drug therapy targets for the treatment of NSCLC patients containing gene mutations, especially EGFR mutations and ALK rearrangements that are targets of the precision medicine management of chest neoplasms [ 149 , 150 ]. A meta-data analysis showed that individuals who never smoked were more susceptible to the EGFR and ALK-EML4 mutations than ever-smokers [ 3 ].…”
Section: The Impact Of Cur Analogs On Nsclcmentioning
confidence: 99%
“…Furthermore, the Asian population-based ALESIA study showed even better efficacy, with an mPFS of 41.6 months and an ORR of 91%. However, despite the significant clinical benefits achieved with alectinib, resistance to alectinib occurred in 53.3% of patients treated with alectinib as the first-line therapy, leading to disease progression, and more progressive disease occurred in second-line alectinib treatment ( 4 , 15 - 17 ). ALK-TKIs resistance mainly arises from ALK mutations and ALK amplification, such as the G1202R mutation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent therapeutic decision-making will be based firstly on the type of progression and secondly on the mechanism of resistance ( 4 , 21 ). Progression can be divided into oligoprogression, central nervous system (CNS) progression, and systemic progression ( 4 , 17 ). Oligoprogression is defined as a tumor disease that progresses in a limited number of sites ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations